Epigenetic histone acetylation modulating prenatal Poly I:C induced neuroinflammation in the prefrontal cortex of rats: a study in a maternal immune activation model - Su, Yueqing; Lian, Jiamei; Chen, Shiyan; Zhang, Wenchang; Deng, Chao (Frontiers in Cellular Neuroscience, 2022)
Neuroinflammation in the central nervous system, particularly the prefrontal cortex (PFC), plays a role in the pathogenesis of schizophrenia, which has been found to be associated with maternal immune activation (MIA). Recent evidence suggests that epigenetic regulation involves in the MIA-induced neurodevelopmental disturbance. However, it is not well-understood how epigenetic modulation is involved in the neuroinflammation and pathogenesis of schizophrenia. This study explored the modulation of histone acetylation in both neuroinflammation and neurotransmission using an MIA rat model induced by prenatal polyriboinosinic-polyribocytidylic acid (Poly I:C) exposure, specifically examining those genes that were previously observed to be impacted by the exposure, including a subunit of nuclear factor kappa-B (Rela), Nod-Like-Receptor family Pyrin domain containing 3 (Nlrp3), NMDA receptor subunit 2A (Grin2a), 5-HT2A (Htr2a), and GABAA subunit β3 (Gabrb3). These results revealed global changes of histone acetylation on H3 (H3ace) and H4 (H4ace) in the PFC of offspring rats with prenatal Poly I:C exposure. In addition, it revealed enhancement of both H3ace and H4ace binding on the promoter region of Rela, as well as positive correlations between Rela and genes encoding histone acetyltransferases (HATs) including CREB-binding protein (CBP) and E1A-associated protein p300 (EP300). Although there was no change in H3ace or H4ace enrichment on the promoter region of Nlrp3, a significant enhancement of histone deacetylase 6 (HDAC6) binding on the promoter region of Nlrp3 and a positive correlation between Nlrp3 and Hdac6 were also observed. However, prenatal Poly I:C treatment did not lead to any specific changes of H3ace and H4ace on the promoter region of the target genes encoding neurotransmitter receptors in this study. These findings demonstrated that epigenetic modulation contributes to NF-κB/NLRP3 mediated neuroinflammation induced by prenatal Poly I:C exposure via enhancement of histone acetylation of H3ace and H4ace on Rela and HDAC6-mediated NLRP3 transcriptional activation. This may further lead to deficits in neurotransmissions and schizophrenia-like behaviours observed in offspring.